VISUAL ADAPTATION OF PATRAKOMALA AS A FASHION MERCHANDISE OF BANDUNG IN KOREAN STYLE - Putri Arsiyana, Nadya
Merchandises are something that are usually brought by someone when traveling to visit a place and have a function to provide a memento of the place visited. Merchandises must have their own characteristics that distinguish them from other merchandises. As a fashion center, Bandung has the potential to develop fashion products as merchandises for its city. Bandung's fashion centers are scattered in various areas, such as the oldest textile center in Bandung, namely Pasar Baru which has been around since 1820, the jeans center in Alley Tamim since 1970, the shoe center in Cibaduyut since 1920, the knitting center on Jalan Binong since 1970 and the center cigondewah fabrics since 1980. The number of textile centers in Bandung has caused the fashion industry such as boutiques, factory outlets and distributions to mushroom so that fashion in Bandung is growing. The development of fashion in the city of Bandung has been influenced by foreign cultures that have entered along with the emergence of fashion trends from outside which have become fashion references in the city of Bandung. This is reinforced by a group of Bandung people who have different characteristics or can be called a multicultural society which makes people accustomed to dealing with different paradigms and views. The flow of globalization has expanded the influence of the Hallyu phenomenon in Bandung, which is gradually being accepted and processed as a new creative adaptation. Bandung requires alternative merchandises products by utilizing the growing Hallyu phenomenon and using visual adaptation approaches to patrakomala as a distinctive visual element of Bandung City to form visual patterns so that these products can easily be accepted by the people of Bandung. The purpose of this research is to identify the influence of the Hallyu phenomenon on fashion products that can be used as a Bandung City merchandises and applied to Korean-style fashion products by adapting the visual variety of patrakomala decorations as a Bandung City merchandises.